Implementación de la contabilidad, comercial para accesorios dy metal de la ciudad de Loja, periodo septiembre 2014 - Chávez Peralta, María Gabriela (2015)
This research paper entitled: IMPLEMENTATION OF BUSINESS ACCOUNTING ACCSESORIOS DyMETAL, OF THE CITY OF LOJA, PERIOD SEPTEMBER 2014, aims to provide a useful accounting tool that will keep proper control of commercial and financial negotiations ACCSESORIOS DYMETAL, control of operations that generate optimal development of the company; this is through real, reliable and timely information to the Financial Statements. It also allows complying with the Regulation of Academic System of the National University of Loja, prior to choose the Bachelor of Engineering in Accounting and Auditing, CPA requirement. They met all objectives, the source documentation, of which the initial information needed was collected to raise the initial inventory, plan and manual accounts are drawn up, the accounting records of the transactions in the general journal was collected, for the treatment of goods has permanent account system, which method involves the use of kárdex cards for inventory control and then the financial statements could establish the economic results of September 2014 were generated was used. With the results the main conclusions and recommendations are presented mainly those relating to follow the implementation of an organized accounting system for the activity performed by the company and to allow access to real information and the time required; comply with tax obligations timely that allow the company framed within the law and have a development around their business objectives.